EndoTOFPET-US: A novel multimodal tool for endoscopy and positron emission tomography - Aubry, N.; Auffray, E.; Mimoun, F. B.; Brillouet, N.; Bugalho, R.; Charbon, E.; Charles, O.; Cortinovis, D.; Courday, P.; Cserkaszky, Aron; Damon, C.; Doroud, K.; et al. (Journal of Instrumentation, 2013)
The EndoTOFPET-US project aims to develop a multimodal detector to foster the development of new biomarkers for prostate and pancreatic tumors. The detector will consist of two main components: an external plate, and a PET extension to an endoscopic ultrasound probe. The external plate is an array of LYSO crystals read out by silicon photomultipliers (SiPM) coupled to an Application Specific Integrated Circuit (ASIC). The internal probe will be an highly integrated and miniaturized detector made of LYSO crystals read out by a fully digital SiPM featuring photosensor elements and digital readout in the same chip. The position and orientation of the two detectors will be tracked with respect to the patient to allow the fusion of the metabolic image from the PET and the anatomic image from the ultrasound probe in the time frame of the medical procedure. The fused information can guide further interventions of the organ, such as biopsy or in vivo confocal microscopy. © 2013 IOP Publishing Ltd and Sissa Medialab srl.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Gamma camera; SPECT; PET PET/CT; coronary CT angiography (CTA); Intra-operative probes; Multimodality systems